Mathematical modeling of drying kinetics and its effect on Brazilian garlic (Allium sativum L.) color (Research, Society and Development, 2020)
Garlic is a product of nutritional importance, with medicinal character, much used, and can be dehydrated for better conservation. However, there is a need for further research to characterize the drying kinetics. The objective of this work was to study drying kinetics of Brazilian garlic (Allium sativum L.), as well as to analyze the effect of the process on the resulting color of garlic. The garlic bulbs were cut into thin slices thicknesses of 2.10-3 and 3.10-3 m, subjected to a drying air temperature of 35, 45, 55 and 70 °C in a mechanical dryer of fixed layer with forced convection. A non-linear regression analysis was performed by the Quase-Newton method to fit 12 mathematical models to the experimental data. The Midilli equation was the one that best characterized all the drying temperatures, for the values collected. The effective diffusivity varied from 1.62 . 10-10  to 6.04 . 10-10 m2 s-1 and 1.60 .  10-10 to 8.36 . 10-10  m2 s-1 at the thickness of 2 . 10-3 and 3 . 10-3 m, respectively. With the increase of the drying air temperature, the samples were darkened in all thicknesses at 70 °C and for the cut thickness of 3 . 10-3 m at 55 °C, also L constant and the hue angle were decreased.